Non-Absorbable Sutures Technique for Distal Patellar Pole Fracture: A Case Report - Reza Zandi; Shahin Talebi; Ahmadreza Ahmadi Abdashti; Mohsen Ghafari (Journal of Orthopedic and Spine Trauma)
Background: Patella fractures account for approximately 1% of all fractures and can be classified as simple or complex. Complex fractures often require surgical intervention due to bone fragment displacement. Rehabilitation focuses on restoring range of motion (ROM), strengthening muscles, and reducing knee stiffness, with recovery potentially taking several months. Treatment options for distal pole patella fractures include fragment resection, which may lead to complications such as patella baja and extensor mechanism weakness. Another method, the basket plate technique, has been associated with discomfort in about 30% of patients, often requiring implant removal surgery. Case Report: We present a novel technique for stabilizing distal pole patella fractures using multifilament polyester non-absorbable coated braided sutures, offering an alternative to traditional fixation methods. Conclusion: This technique provides stable fixation while avoiding the need for implant removal. Although further research is required to compare its efficacy with conventional approaches, initial results suggest it may be a promising option for managing distal pole patella fractures